Shuggie Bain - Stuart, Douglas, 1976- (London : Picador, 2020)
"Shuggie Bain is the unforgettable story of young Hugh "Shuggie" Bain, a sweet and lonely boy who spends his 1980s childhood in public housing in Glasgow, Scotland. Thatcher's war on heavy industry has put husbands and sons out of work, and the city's notorious drugs epidemic is waiting in the wings. Shuggie's mother Agnes walks a wayward path: she is Shuggie's guiding light but a burden for his artistic brother and practical sister. She dreams of a house with its own front door while she flicks through the pages of the Freemans catalogue, ordering a little happiness on credit, anything to brighten up her grey life. Married to a "whoremaster" of a husband, Agnes keeps her pride by looking good-her beehive, make-up, and pearly-white false teeth offer a glamourous image of a Glaswegian Elizabeth Taylor. But under the surface, Agnes finds increasing solace in drink, and she drains away the lion's share of each week's benefits-all the family has to live on-on cans of extra-strong lager hidden in handbags and poured into tea mugs. Agnes's older children find their own ways to get a safe distance from their mother, abandoning Shuggie to look after her as she swings between alcoholic binges and sobriety. He is meanwhile doing all he can to somehow become the normal boy he desperately longs to be, but everyone has realized that Shuggie is "no right," and now Agnes's addiction has the power to eclipse everyone close to her-even and especially her beloved Shuggie. A heartbreaking novel of addiction, sexuality, and love, Shuggie Bain is an epic portrayal of a working-class family that is rarely seen in fiction"--
AAL
R K Corporation
Booker Prize for Fiction, 2020.
Keywords: Working class families -- Scotland -- Glasgow -- Fiction